"People" can be better than "you": The moderating role of regulatory focus on self-referencing messages in physical activity promotion campaigns among college students. Issue 3 (3rd July 2017) - Lee, Seungae; Mackert, Michael
ABSTRACT: Self-referencing effects explain why many advertisements try to relate people with the ads; when an individual relates an ad to the self, the person will be more likely to recall the ad. However, this study revealed that the regulatory focus of messages is a boundary condition for self-referencing strategy. Self-referencing did not yield a positive persuasion effect in prevention-focused messages. The underlying message process analyses further revealed people avoid elaborating prevention-focused messages when used with self-referencing, rather than viewing them in a biased manner. The findings provide guidance for health communication practitioners' use of self-referencing statements.